(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: This study aimed to assess of diabetes patient adherence to dietary recommendation in Diabeticscenter in Al-Najaf city and to find out the relationship between the diabetic patient adherence to dietaryrecommendation and their demographic and clinical data. Methodology: Descriptive analytic design wascarried out to assess of diabetics patient adherence to dietary recommendation in Al-Najaf City/ HealthDirectorate of Al-Najaf Al-Ashraf / Al-Sadder Medical City / Al-Najaf Center for Diabetes and Endocrine.The study was carried out from February 1st, 2018 up to March 28th, 2018. A non-probability (accidental)sampling technique was used consisting of (100) female and male those who visit Al-Najaf Center forDiabetes and Endocrine. Data collected through using of a well-designed questionnaire consist of threeparts: Part I: Socio-demographic Characteristics, Part II: Clinical Data: consists of (6) items and Part 111:Patient adherence to dietary recommendation. This part of the questionnaire consists of (16) items.Conclusion: It is concluded that the Majority of the stay sample have fair adherence to diabetics dietaryrecommendations.Recommendation: Based on study conclusion, its need for a good relationship between the patient andhealth- care provider in order to provide more understanding and knowledge about the disease and its nonmedical management and diabetic’s patients need dietary recommendations with means of education, suchas published materials with regard to dietary regimen.